Penerapan Problem Based Learning dan Culturally Responsive Teaching untuk Meningkatkan Hasil Belajar Materi Lingkaran - Irmayana, Irmayana; Junaidi, Junaidi; Maksud, Maksud (Mandalika Mathematics and Educations Journal, 2025)
Abstract This study was motivated by the low learning outcomes of students on the topic of circles in class VIII-A of SMP Negeri 2 Mataram. The aim of this research was to improve students' mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model integrated with the Culturally Responsive Teaching (CRT) approach. This study was conducted as Classroom Action Research (CAR) carried out in three cycles, each consisting of the stages of planning, implementation, observation, and reflection. The CRT approach was applied by developing student worksheets (LKPD) that reflected local culture and students’ daily experiences, as well as using contextual PowerPoint-based media. Data were collected through learning outcome tests and observation of student activities. The results showed an increase in students’ average scores from 49.42 in the pre-cycle to 83.02 in the third cycle, with the percentage of classical completeness increasing from 13.95% to 86.04%. In addition to cognitive improvement, student engagement during the learning process also showed positive development. The implementation of the PBL model combined with the CRT approach proved to be effective in creating meaningful, contextual, and relevant mathematics learning experiences for students.